Decomposing Inequality in CO2 Emissions: the Role of Primary Energy Carriers and Economic Sectors - Nicole Grunewald; Michael Jakob; Ioanna Mouratiadou (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Emission inequality across countries and the contribution of the energy mix and the sectoral composition of a country s energy use are of central importance to the climate debate. We analyze the evolution of inequality in global CO2 per capita emissions using both historical data on energy-related CO2 emissions and future emission scenarios generated with the integrated assessment model REMIND. Within our sample of 90 countries the results indicate that the Gini index declined from about 0.6 in 1971 to slightly above 0.4 in 2008. A decomposition of the Gini index of total emissions into primary energy carriers and into economic sectors provides additional insights. From the perspective of primary energy carriers, it is indicated that this reduction is mainly attributed to declining shares of emissions from coal/peat and oil in total emissions, and decreasing emission inequality within all fossil primary energy sources. From the perspective of economic sectors, the decline in overall inequality is almost entirely due to a pronounced decline of the contribution of emissions from manufacturing & construction. Our analysis also suggests that an equally spread emission reduction from any one source (i.e. primary energy carrier or economic sector) would not have a major impact on overall emission inequality. The analysis of future scenario data indicates that climate policy reduces absolute emissions inequality, while inducing drastic progressive emission reductions in all regions
Keywords: Q43; Q48; D63; 330